Study of the Ability of Radiation in Treating Cancer - Karim, Muhammad Kadim; Kadam, Hiba Jawad; Muslim, Muslim Mohanaad (American Journal of Botany and Bioengineering, 2024)
Radiation therapy (RT) has emerged as one of the most effective treatment modalities for cancer, with nearly 50% of patients requiring it during their treatment course and contributing to 40% of curative outcomes. Its primary goal is to inhibit cancer cell proliferation through targeted DNA damage while sparing surrounding healthy tissues. Over the last century, advancements in imaging, radiobiology, and treatment delivery have enhanced its effectiveness. This review explores the principles, applications, and advancements in radiotherapy, emphasizing its role in improving cancer survival rates and mitigating side effects.